Multifunctional Microgels for Direct, Multiplexed and High Sensitive Detection. (2017) - Battista, Edmondo; Causa, Filippo; Cusano, Angela Maria; Di Natale, Concetta; Scognamiglio, Pasqualina Liana; Mazzarotta, Alessia; Celetti, Giorgia; Cosenza, Chiara; Aliberti, Anna; Netti, Paolo Antonio
Abstract: Detection of tiny quantities of nucleic acids, protein biomarkers and small organic molecules directly in complex matrices is of key relevance both in biomedical and in environmental fields. Moreover direct quantification of clinically relevant molecules (such as miRNA, DNA or proteins) in plasma is difficult due to its heterogeneous composition and the low amounts of target molecules. As for environmental pollutants (i.e. Aflatoxins), the direct detection is also hampered by the complexity of liquid samples (milk, wine, waste waters) lowering the sensitivities and requiring several steps of targets isolation and purification. Here we present our material platform based on microgels and hydrogel microparticles featuring high flexibility in performing detection and harvesting of different kind of targets in complex solutions.